Chemistry and crime : from Sherlock Holmes to today's courtroom - Gerber, Samuel M., 1920-; American Chemical Society (Washington, D.C. : American Chemical Society, 1983)
Discusses the application of the principles of chemistry for committing crimes and for tracking down criminals in literature and the state of the art in the field of forensic science.
Papers from a symposium, Chemistry in Crime--Fact and Fiction.
Includes bibliographical references and index.
Young Adult.
Young Adult
Keywords: Chemistry, Forensic -- History; Detective and mystery stories, English -- History and criticism; Science in literature; Chemistry -- History; Medical jurisprudence; Mystery fiction -- History and criticism; Science in literature